Effect of Topical Application of Dentol Drop on the Success of Inferior Alveolar Nerve Block for Teeth with Irreversible Pulpitis: A Double-blind Randomized Clinical Trial - Sharifi, Roohollah; Godiny, Mostafa; Mozaffari, Hamid Reza; Safaei, Mohsen; Hatam, Reza; Veisi, Mahta (Iranian Endodontic Journal, 2019)
Introduction: The failure rate of inferior alveolar nerve (IAN) block is high for mandibular molars with irreversible pulpitis. This double-blind, randomized, clinical trial aimed to assess the effect of topical application of Dentol drop on the rate of successful anaesthesia of mandibular molars with irreversible pulpitis due to deep carious lesions. Methods and Materials: Seventy-two patients with mandibular first and second molars with irreversible pulpitis and deep cavitated carious lesions participated in this study. The patients were randomly assigned to the test and control groups (n=36). In the test group, a cotton pellet, dipped in Dentol drop, was placed in the cavity for 10 min. A placebo was used _in the same manner_ in the control group. Level of pain was measured before the intervention, 15 min after anaesthesia (when patients reported numbness at the corner of the mouth), during access cavity preparation, upon pulp exposure and after introduction of the initial file into the root canal; using a Heft-Parker “Visual Analog Scale” (VAS). Data were analysed using ANCOVA. Results: Levels of pain were recorded during access cavity preparation (P<0.001), pulp exposure (P<0.001) and file introduction into the canal (P=0.018). In the test (Dentol) group, the obtained levels of pain were significantly lower than those of the corresponding values in the control group. Conclusion: Topical application of Dentol drop increased the success rate of IAN block for root canal treatment of mandibular molars with irreversible pulpitis. Keywords: Dentol Drop; Inferior Alveolar Nerve Block; Irreversible Pulpitis